Local Press Pages Are A Source Of Studying The History Of Bukhara Emirate - Nosirov Sherzod O‘ktam o‘g‘li (Western European Studies, 2024)
This article analyzes the pages of the local press as one of the sources of studying the Bukhara Emirate. For the study of the history of Bukhara Emirate, newspapers and magazines, which are press pages published not only in the regions of Bukhara Emirate, but also in other regions of Turkestan, are a mirror of objective history. The history of the Bukhara Emirate is covered by the analysis of other press pages, such as newspapers and magazines, published in the country.
Keywords: press; the; newspaper; magazine